Differences in gloss value of temporary crown materials acrylic resin and composite resin before and after brushing with whitening toothpaste - Stepaninta STEPANINTA; Ika ANDRYAS (Journal of Syiah Kuala Dentistry Society, 2022)
The temporary crown must meet the patient's aesthetic needs even if it is used only for a while,especially gloss. It is believed that composite resin does not produce odor but shows minimal shrinkage, lower heatgenerated during polymerization, and is more aesthetically pleasing. Therefore, this material is one of the choices sothe clinicians can improve the patient's aesthetic needs. Nowadays, people demand clean and whiter teeth. Brushingwith whitening toothpaste is believed to affect the surface of the composite resin. The design of this study was alaboratory experiment. The sample in this study was a temporary crown material of acrylic resin and selfpolymerized composite resin with a sample size of 26 mm x 26 mm x 2 mm. All samples were tested using a gloss meter, followed by univariate statistical analysis to determine each group's mean gloss value and standard deviation. The research was continued using Wilcoxon statistical analysis to determine the difference in each group's temporary crown material gloss value. The results showed a significant difference in all temporary crown materials gloss value before and after brushing with whitening toothpaste. The conclusion of this study state that the composite resin material group has a better gloss value than acrylic resin material. Composite resin can maintain gloss value at gloss standard, even after brushing with abrasive toothpasteKEYWORDS: Temporary crown, Gloss, Gloss Meter